2019
DOI: 10.2134/agronj2018.12.0795
|View full text |Cite
|
Sign up to set email alerts
|

Root Growth and Architecture Responses of Bread Wheat Cultivars to Salinity Stress

Abstract: The screening of genotypes that perform better in saline soils is important for food security as the arable land affected by this problem is increasing. To mimic the conditions found in saline fields, a saline soil‐based screening method was developed to distinguish genetic diversity in root growth responses and shoot growth rates of bread wheat (Triticum aestivum L.) cultivars, namely Roshan, Bam, Tabbasi, Mahooti, Shiraz, Qods, Falat, and Atrak. Soil‐filled polyvinyl chloride (PVC) tubes perfused with 50 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Salinity stress is one of the critical determinants limiting crop production (Ali et al., 2019; Ibrahim et al., 2018; Rahnama, Fakhri, & Meskarbashee, 2019), and it is expected that 50% of the world's arable area will be affected by salinity by 2050 (Machado & Serralheiro, 2017). Salinity stress affects crop growth by osmotic stress and/or specific ion toxicities.…”
Section: Introductionmentioning
confidence: 99%
“…Salinity stress is one of the critical determinants limiting crop production (Ali et al., 2019; Ibrahim et al., 2018; Rahnama, Fakhri, & Meskarbashee, 2019), and it is expected that 50% of the world's arable area will be affected by salinity by 2050 (Machado & Serralheiro, 2017). Salinity stress affects crop growth by osmotic stress and/or specific ion toxicities.…”
Section: Introductionmentioning
confidence: 99%
“…This concluded that aerial application of the salt had triggered the growth of the root. Plants driving for water due to salinity stress have an elongated and dense root system (Rahnama et al, 2019). Therefore, we can deduce that at a moderate concentration of salt, the maize plant enhanced its root system at the expense of the shoot system (Ma et al, 2021).…”
Section: Resultsmentioning
confidence: 95%
“…Salinity is one of the main environmental factors that lead to the degeneration of agricultural land and a decrease in crop productivity worldwide (Ali et al, 2018;Rahnama et al, 2019), especially in arid and semi-arid areas. It is expected that by 2050 salinity will affect 50% of the world's arable areas (Machado and Serralheiro, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…It is expected that by 2050 salinity will affect 50% of the world's arable areas (Machado and Serralheiro, 2017). The effect of salinity in arid and semiarid areas is more serious, which influences seed germination, early growth stages and consequently crop production (Ali et al, 2018;Rahnama et al, 2019). Salinity is known to have multiple effects on plant growth through osmotic impact on plant water imbibition and/or specific ion toxicities (Hirich et al, 2014).…”
Section: Introductionmentioning
confidence: 99%